Winn Newman papers - Newman, Winn, 1924-1994.
Correspondence, legal briefs, depositions, orders, motions, exhibits, transcripts, speeches and writings, subject files, biographical material, school and family papers, and printed material documenting Newman's career as an attorney practicing chiefly in Washington, D.C., and specializing in employment discrimination cases and labor law. Includes material on opposition to the nomination of Clarence Thomas to the Supreme Court in 1991; litigation involving the rights of women and minorities; lawsuits on behalf of AFSCME (American Federation of State, County, and Municipal Employees) involving the comparable worth of female employees; and cases involving pregnancy discrimination, union access to employer equal opportunity data, job evaluation, pay equity, and sex and race wage discrimination. Other clients include American Association of Retired Persons; Americans for Democratic Action; International Union of Electrical, Radio, and Machine Workers; International Union, United Automobile, Aerospace, and Agricultural Implement Workers of America; New York Hotel and Motel Trades Council; and Service Employees' International Union. Other organizations with which Newman was associated include Montgomery County (Md.) Compensation Task Force, National Committee on Pay Equity, and National Organization for Women.
Lawyer. Named Irwin Newman; known as Winn Newman since 1946.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Thomas, Clarence, -- 1948-; AFSCME; American Association of Retired Persons; Americans for Democratic Action; International Union of Electrical, Radio and Machine Workers; International Union, United Automobile, Aerospace, and Agricultural Implement Workers of America; Montgomery County (Md.). -- Compensation Task Force; National Committee on Pay Equity; National Organization for Women; New York Hotel and Motel Trades Council; Service Employees International Union; United States. -- Supreme Court; Affirmative action programs -- United States; Discrimination in employment -- Law and legislation -- United States; Equal pay for equal work -- United States; Job evaluation -- Law and legislation -- United States; Labor laws and legislation -- Cases -- United States; Minorities -- Legal status, laws, etc. -- United States; Pay equity -- United States; Pregnant women -- Employment -- Law and legislation -- United States; Sex discrimination in employment -- United States; Wages -- Maryland; Wages -- United States; Women -- Legal status, laws, etc. -- United States; Women's rights -- United States; Lawyers